Construction of The Diagnostic Test Instrument Heat and Temperature Conception Four-Tier Test: An Exploratory Study - Destiani, Rinta; Ramalis, Taufik Ramlan; Sari, Ika Mustika (Universitas Lambung Mangkurat, 2024)
Students regard physics as challenging due to the difficulty of integrating knowledge learned before and after the lesson, which causes misconceptions. One such misconception pertains to the subject of temperature and heat. The objective of this study is to develop a four-tier diagnostic test instrument that can be used to identify concepts regarding heat and temperature. This study employed Rasch analysis as a mixed method. The unidimensionality of the instrument is very good at 50.3%, with a person measure of -0.39 and an Alpha Cronbach of 0.82, which suggests a strong interaction between the person and the details of the question as a whole. The consistency of the responses from students is adequate, as indicated by a person reliability of 0.80 and an item reliability of 0.99. However, the items' quality and the instrument's reliability are exceptional. The Outfit MNSQ Person and Item of 0.99 and the Outfit ZSTD with a value of 0.02 suggest that the quality is improving. The instrument includes ten questions that can be employed to identify students' conceptions. The utilization of this instrument has the potential to yield more comprehensive measurement results regarding students' misconceptions.